Good Practices in Pursuit of Sustainable Rural Transformation - Rabinowicz, Sarit Grinberg; Chinapah, Vinayagum (Journal of Education and Research, 2015)
Responding to the world’s instability in the economy, society, and in the environment, initiatives such as the EFA goals and MDGs acknowledge that the developing world is in crisis. For the rural people, who are the majority of the poor worldwide, economic, social, and environmental instability is a daily reality. Rural people are among the most vulnerable, the most marginalized, and the most oppressed groups and they make up the majority of the poor in most countries.  With education as a catalyst for transformation, providing the rural people with the knowledge, skills, and tools they need to improve their lives, and taking into account the context and reality of rural people, sustainability has to be a part of this transformation process.  Sustainable rural transformation as a holistic perspective takes into account rural needs, the context, and the process of transformation. This paper identifies the challenges that rural populations are facing, and argues how the concept and practice of education for rural transformation should work towards a sustainable development, envisioning a ‘sustainable rural transformation’. This paper illustrates and examines the concept of sustainable rural transformation and why education and good practices are important to promote an equitable sustainable rural transformation and human well-being.